The Rate of Modelling the Change of Hydrodynamic Components and Ecosystem Degradation due to the Existence of Coastal Reclamation Research in 2012-2022 - Subiyanto, Subiyanto; Putri, Nabilla Azka; Tofany, Novan; Ahmad, Mohammad Fadhli; Supian, Sudradjat (Research Collaboration Community (Rescollacom), 2024)
Reclamation is defined as an action made to increase the use of land resources while considering environmental and socioeconomic factors, such as landfilling and land drainage. Unfortunately, as man-made structures in the waters, coastal reclamation has the potential to significantly caused a disruption towards nature processes. This research aims to examine the pace of inquiry into the negative effects of coastal reclamation. The search was conducted using Publish or Perish Software, which was used to choose data sources in the form of Google Scholar from 2012-2022, and we applied a systematic Literature Review method. Identification and evaluation were carried out using two types of software such as Publish or Perish and VOSviewer. This research showed that China and India are the most frequent countries to be chosen as the area of interest related to this topic due to their experiences in handling a lot of coastal reclamations in their territorial. Mean-while, other countries such as Indonesia, Singapore, Malaysia, Philippines and some Europe Countries counted as the low rate areas for this type of publication even though they had a huge number of similar projects.